2021
DOI: 10.1002/glia.24052
|View full text |Cite
|
Sign up to set email alerts
|

Activated microglia do not increase 18 kDa translocator protein (TSPO) expression in the multiple sclerosis brain

Abstract: To monitor innate immune responses in the CNS, the 18 kDa Translocator protein (TSPO) is a frequently used target for PET imaging. The frequent assumption that increased TSPO expression in the human CNS reflects pro‐inflammatory activation of microglia has been extrapolated from rodent studies. However, TSPO expression does not increase in activated human microglia in vitro. Studies of multiple sclerosis (MS) lesions reveal that TSPO is not restricted to pro‐inflammatory microglia/macrophages, but also present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 45 publications
(77 reference statements)
2
44
0
Order By: Relevance
“…Similarly, although TSPO has been used as a proxy for microglia activation, the functional consequences of increased TSPO are not entirely understood [ 209 ]. In fact, PET imaging studies conducted in patients with MS show no difference in TSPO expression between activated macrophages in white matter lesions and those in normal appearing white matter or in healthy controls [ 210 ]. Other studies have indicated additional confounds to consider in TSPO studies, namely that TSPO tracers are bound by vascular endothelia and TSPO levels show maximal intensity after the resolution of inflammation [ 211 , 212 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, although TSPO has been used as a proxy for microglia activation, the functional consequences of increased TSPO are not entirely understood [ 209 ]. In fact, PET imaging studies conducted in patients with MS show no difference in TSPO expression between activated macrophages in white matter lesions and those in normal appearing white matter or in healthy controls [ 210 ]. Other studies have indicated additional confounds to consider in TSPO studies, namely that TSPO tracers are bound by vascular endothelia and TSPO levels show maximal intensity after the resolution of inflammation [ 211 , 212 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that TSPO is also expressed by other cell types such as astrocytes or glial progenitor cells and thus cannot be seen as a microglia-specific radiotracer target. Moreover, a recent study could show that the findings from animal models do not always translate to the clinical context in humans [47]. Despite the fact that existing radiotracers need further improvement, the approach holds great promise for patients with (suspected) CNS pathologies.…”
Section: Non-invasive Imaging Techniques For Microglia Analysesmentioning
confidence: 99%
“…For example, recent publications have challenged longstanding assumptions by proposing that an increase in TSPO PET signal under proinflammatory conditions correlates to increased microglial density rather than the upregulated expression of the protein in humans. [60,61] Moreover, the longstanding assertion that increased TSPO expression is correlated only with microglial activity has been repeatedly challenged, with several studies also detecting its presence in astrocytes and endothelial cells. [62] Furthermore, a key gap in our knowledge is the lack of an atomic structure of human TSPO, with many researchers relying on structures of mouse [63] or bacterial [64] TSPO to construct homology models to guide their work.…”
Section: Summary and Future Directionsmentioning
confidence: 99%